Modelo lógico da sinergia entre sinalização TGF_ e dano ao DNA no destino celular - Rossato, Veronica Venturini (2017)
Many factors may cause damages to the DNA, among them we can quote environmental pollution, ionizing radiations, amongst others. The signalization involved after an instituted damage consists in activation pathways and/or inhibitions, and the cellular answers after the damage include a removal of it, activation of cell cycle checkpoints, senescence or apoptosis. All of these processes are ruled by specific proteins that perform their functions to ensure that the stages of the cellular cycle are completed before the cellular division. Many studies suggest that senescent cells release factors that induce permanent senescence as a bystander effect in the cellular environment. These factors are known as SMS (Senescence-messaging secretome), and among it, TGF is a component involved in the called “senescence bystander”. This work deals with a proposed regulatory network for the interaction between proteins involved in the pathways of DNA damage responses and proteins involved in TGF pathway signaling, in addition to a protein interaction network proposed by Mombach et al. 2015. In the logical model proposed here, the variables that represent the proteins are discrete and the interactions between them are represented by logical operators (AND, OR and NOT) used in the rules of interactions. The inputs of the models are: expression of the TGF pathway in different levels, single strand breaks or doubles of the DNA (SSB – Single Strand Breaks and DSB – Double Strand Breaks) reparable or irreparable, and as outputs we have the phenotypes of senescence, apoptosis, cell cycle arrest and proliferation. The network was submitted to mutations simulating loss and gain of protein functions using the GINsim 2.9.4 software. These simulations show consistency with experimental works in phenotypes of cellular growth obtained from mutant cells. We observed as well the effect of synergy of the inputs of the system, which gave us as answer an increase of induction of senescence and cellular apoptosis. Approach the different functions of the TGF pathway in synergy with proteins involved in the DNA damage signaling, as well as evaluate the phenotypes occasioned by this combinations of interactions may be important therapeutic strategies in the treatment of pathologies, for example cancer.